Características y perspectivas de la producción porcina en Colombia. - Trujillo, C.; Santos, J.; Beltrán B, L.E.; Buitrago Arbeláez, J.; Gómez, G. (Cooperativa Nacional de Zootecnistas, 2018)
Porcicultura